Kepuasan Kerja Guru Secara Optimal Dalam Proses Belajar Mengajar di Sekolah Dasar - Marwan; ibrahim; Mohd. Isya Awang; Sufriadi (Yayasan Hurriah, Banda Aceh, 2021)
English: It is appropriate for a teacher to have positive enthusiasm and motivation in carrying out daily tasks so that a sense of pleasure arises in carrying out the profession as an educator or teacher. The criteria for teachers who have high motivation to teach have good competence and are happy with the work they do in a school or campus environment. Good and quality school management can support the performance of teachers in carrying out their activities and have the aim of improving the quality and achievement of student learning. Support from school principals, school committees, students and parents is very much needed in optimizing teacher performance for teaching and learning activities. There are about 76% of students who strongly support teacher activities and 83% of school principals support so that teachers are able to personally improve the quality of teaching in schools. Bahasa: Selayaknya bagi seorang guru memiliki semangat dan motivasi positif dalam melakukan tugas sehari-hari agar muncul rasa senang dalam menjalankan profesi sebagai pendidik atau pengajar. Kriteria guru yang memiliki motivasi tinggi untuk mengajar mempunyai kompetensi yang baik dan senang dengan pekerjaan yang dia lakukan dalam lingkungan sekolah atau kampus. Manajemen sekolah yang baik dan berkualitas dapat mendukung kinerja guru dalam melakukan aktivitasnya serta punya tujuan meningkatkan kualitas serta prestasi belajar siswa. Dukungan dari kepala sekolah, komite sekolah, siswa dan orang tua wali sangat diperlukan dalam mengoptimalkan kinerja guru untuk kegiatan belajar mengajar. Terdapat sekitar 76% siswa sangat mendukung aktivitas guru dan 83% dukungan kepala sekolah agar guru mampu meningkatkan kualitas secara personal dalam mengajar di sekolah.